Assessment of safe bioactive doses of Foeniculum vulgare Mill. essential oil from Portugal. Issue 22 (17th November 2017) - Cabral, C.; Miranda, M.; Gonçalves, M. J.; Cavaleiro, C.; Cruz, M. T.; Salgueiro, L.
Abstract: This study was designed to evaluate the antifungal activity of Foeniculum vulgare essential oil; concomitantly, the safety of bioactive doses was also unveiled, for the first time, in several mammalian cells. The chemical characterisation was made by GC and GC–MS. Antifungal activity was evaluated against yeasts, dermatophytes and Aspergillus strains and germ tube inhibition assay was evaluated using Candida albicans . Cell viability was assessed by the MTT assay. The main constituents of the oil are E-anetol (47%), α -phellandrene (11%), α -pinene (10.1%) and fenchone (10.8%). The oil was more active against Cryptococcus neoformans and C. albicans (MICs 0.32–0.64 μL/mL) and the filamentation of C. albicans was totally inhibited with 0.08 μL/mL. The oil is safe for keratinocytes, hepatocytes and fibroblasts in concentrations up to 1.25 μL/mL, and to macrophages up to 0.64 μL/mL. These findings highlight safe bioactive concentrations that should be deeper investigated for further application in pharmaceutical industry. Abstract :